A Patient with Beta-Propeller Protein-Associated Neurodegeneration: Treatment with Iron Chelation Therapy - Lim, Shen-Yang (J Mov Disord, 2018)
We present a case of beta-propeller protein-associated neurodegeneration, a form of neurodegeneration with brain iron accumulation. The patient harbored a novel mutation in the WDR45 gene. A detailed video and description of her clinical condition are provided. Her movement disorder phenomenology was characterized primarily by limb stereotypies and gait dyspraxia. The patient’s disability was advanced by the time iron-chelating therapy with deferiprone was initiated, and no clinical response in terms of cognitive function, behavior, speech, or movements were observed after one year of treatment.